Hanukkah : a counting book in English, Hebrew, and Yiddish - Sper, Emily (New York : Scholastic, 2001)
Lets children count each night of the Festival of Lights in English, Hebrew, and Yiddish, with colorful die-cut candles and symbols that explain the story of Hanukkah.
.5
K-3
Text in English, Hebrew, and Yiddish.
"Cartwheel books."
Die-cut pages.
Keywords: Hanukkah -- Juvenile literature; Counting -- Juvenile literature; Toy and movable books -- Specimens; Hanukkah; Holidays; Hebrew language materials -- Bilingual; Yiddish language materials -- Bilingual; Counting; Toy and movable books; Hanukkah; Holidays; Bilingual books -- English-Hebrew.; Bilingual books -- English-Yiddish.; Counting; Toy and movable books